Lemnos and Gallipoli: Towards redressing a marginalised history - Yiannakis, John (Black Swan Press, 2014)
Despite the island of Lemnos being just 100 kilometres from the Gallipoli peninsula and having played a crucial role in the eight month Dardanelles campaign, the island is virtually unknown to most Australians. While much has been written about Gallipoli, Lemnos is not included in this discourse having been marginalised over time. How important was Lemnos to the Gallipoli campaign? What social, political, economic and technological effect did the arrival of 20th century technologies have on the people and structures of a remote Greek island that still functioned as a rural subsistence community? What do we know about the relationships that developed between the locals and the foreigners, notably the Anzacs?